2000
DOI: 10.1128/jvi.74.17.8018-8027.2000
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Infection of Endothelial Cells by Avian Influenza Virus A/FPV/Rostock/34 (H7N1) in Chicken Embryos

Abstract: The tissue tropism and spread of infection of the highly pathogenic avian influenza virus A/FPV/Rostock/34 (H7N1) (FPV) were analyzed in 11-day-old chicken embryos. As shown by in situ hybridization, the virus caused generalized infection that was strictly confined to endothelial cells in all organs. Studies with reassortants of FPV and the apathogenic avian strain A/chick/Germany/N/49 (H10N7) revealed that endotheliotropism was linked to FPV hemagglutinin (HA). To further analyze the factors determining endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 43 publications
7
76
0
2
Order By: Relevance
“…Using another HPAIV of subtype H7, we have previously shown that endotheliotropism plays a crucial role in systemic infection of the chicken embryo. 22,31 In the present study, there was no evidence for infection of endothelia in any of the analyzed organs. Thus, endotheliotropism can be ruled out as a mechanism promoting systemic spread of SC35M infection in mice.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Using another HPAIV of subtype H7, we have previously shown that endotheliotropism plays a crucial role in systemic infection of the chicken embryo. 22,31 In the present study, there was no evidence for infection of endothelia in any of the analyzed organs. Thus, endotheliotropism can be ruled out as a mechanism promoting systemic spread of SC35M infection in mice.…”
Section: Discussionmentioning
confidence: 68%
“…22 Linearization of this plasmid with HindIII and subsequent T7 RNA polymerase transcription produced an antisense RNA probe suited to detect NP-specific RNA. Control RNA probes were obtained from the vector containing the dual-promoter plasmid of coxsackievirus B3 (pCVB3-R1).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Given that both selectins and their ligands are evolutionary conserved molecules, one can predict expression of Su-SLe x on avian endothelial cells. Interestingly, three previous reports described a strong HA-dependent tropism of H5 and H7 poultry influenza viruses to endothelial cells of chicken embryo cells (13) and to cultured human pulmonary microvascular endothelial cells (45,69). Thus, enhanced binding of poultry influenza viruses to Su-SLe x and other sulfated and fucosylated sialyloligosaccharide sequences could have emerged as an adaptive change required for viral endotheliotropism in birds, a wellknown feature of highly pathogenic poultry influenza viruses with H5 and H7 HA (28).…”
Section: Discussionmentioning
confidence: 99%
“…2 When prominent, this leakage corresponds to extremely high cytokine levels in the tissues (cytokine storm). 162 Although some studies have described receptors for influenza virus on the surface of human endothelial cells 170 and virus infection of avian 28,65 and human endothelial cells, 175 these studies suggest the endothelial cell damage is due to cytokines. Influenza virus infection of endothelial cells in swine lungs has not been documented.…”
Section: Immunopathologymentioning
confidence: 99%